On the distribution network narrowband noise statistics. - Sabolic, D.
Based on measurement results, we present statistical description of the narrowband noise on an indoor low voltage distribution power network. Experiments of limited nature were carried on two locations of different kinds: an office building in the city centre and a residential house in a suburban area. They were also done during working and nonworking hours, weekends, and night time. The results have preliminary nature, and further measurements will be required. We limit our observations on amplitude distributions and distributions of interference-free frequency intervals. From our measurement we can derive simple models for these distributions.
Keywords: Amplitude distributions; City centre; Distribution network; Indoor low voltage distribution network; Interference-free frequency intervals; Narrowband noise statistics; Night time; Nonworking hours; Office building; Residential house; Suburban area; Weekends; Working hours